Respuesta :

Answer:

TRUE. We need to use the chain rule to find the derivative of the given function.

Step-by-step explanation:

Chain rule to find the derivative,

We have to find the derivative of F(x)

If F(x) = f[g(x)]

Then F'(x) = f'[g(x)].g'(x)

Given function is,

y = [tex]\sqrt{2x+3}[/tex]

Here g(x) = (2x + 3)

and f[g(x)] = [tex]\sqrt{2x+3}[/tex]

[tex]\frac{dy}{dx}=\frac{d}{dx}(\sqrt{2x+3}).\frac{d}{dx} (2x+3)[/tex]

y' = [tex]\frac{1}{2}(2x+3)^{(1-\frac{1}{2})}.(2)[/tex]

   = [tex](2x+3)^{-\frac{1}{2}}[/tex]

y' = [tex]\frac{1}{\sqrt{2x+3}}[/tex]

Therefore, it's true that we need to use the chain rule to find the derivative of the given function.